EFEKTIFITAS TEPUNG DAUN EBONI (DIOSPYROS CELEBICA) TERHADAP MORTALITAS RAYAP TANAH SHEDORHINOTERMES SP. PADA SKALA LABORATORIUM - Nurwansyah, M; Erniwati, .; Mutmainnah, . (Universitas Tadulako, 2018)
Termites are large scale insects that have caused enormous economic losses. Termites that cause the most damage to the plants of Forestry, Plantation and Agriculture are Shedorhinotermes sp termites. This study was conducted in October until November 2016 at Hama Laboratory and Plant Disease (HPT) of Agriculture Faculty, Tadulako University. This study used Completely Randomized Design (RAL) with 5 treatments P0 P1 P2 P3 P4 and it was repeated 4 times, so that there are 20 units of experiments and each unit of experimental consists of 20 tail termites, then it takes 400 tail of termites. Observation result of the initial time of death, time of death 50% and and death 100 % of termites showed that the application of eboni leaf flour gives significance effect toward mortality, where P4 showed the fastest time of death are 8 hours (initial death), 15 hours (death 50%), 23,5 hours (death 100%). Observation of termites mortality test 12 hours after the treatment of the application also showed that the application of ebony leaf flour gave a significant effect toward the mortality of termite testing where P4 provides an increase in mortality that reaching 3,7%.Â Keywords: Ebony Leaf (Diospyros celebica), Termite, Mortality.Â EFEKTIFITAS TEPUNG DAUN EBONI (DIOSPYROS CELEBICA) TERHADAP MORTALITASRAYAP TANAH SHEDORHINOTERMES SP. PADA SKALA LABORATORIUM.